Auctioning off a favour: corruption and lobbying in a combo model - Carsten Gerrits; Klaus Beckmann (Verein für Socialpolitik, 2010)
It is the prevailing approach in the public choice literature to model lobbying and corruption in the same manner. On the contrary, we attempt to capture both in the same framework (auction theory), but using different modelling approaches. We present a unified framework in which some interesting conclusions ensue, not the least the possibility of a benign view on corruption as in Besley (2006).
Keywords: D72; D73; K42; 330